2007
DOI: 10.1002/adma.200602398
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ti–Al Micro/ Nanometer‐Sized Porous Alloys through the Kirkendall Effect

Abstract: Porous metals are of great interest as a potential engineering material in various industrial fields because of their unique properties such as their impact energy absorption capacity, their gas and liquid permeability, thermal conductivity, and electrical insulating properties.[1] However, their poor oxidation resistivity, poor corrosion resistance, and intolerance at elevated temperatures restrict their potential applications in much wider fields, such as high-temperature gas separation and as catalysis in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(96 citation statements)
references
References 24 publications
2
94
0
Order By: Relevance
“…First, Fe 2 Al 5 forms at the interface between aluminum and iron powders by solid state interdiffusion below 648°C [20]. Simultaneously, pores are formed because of the different intrinsic diffusion coefficients of Al in Fe and Fe in Al, based on the Kirkendall effect [14]. In addition, the intensity of the reaction decreases due to decrease of the iron / aluminum contact area and the content of aluminum [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, Fe 2 Al 5 forms at the interface between aluminum and iron powders by solid state interdiffusion below 648°C [20]. Simultaneously, pores are formed because of the different intrinsic diffusion coefficients of Al in Fe and Fe in Al, based on the Kirkendall effect [14]. In addition, the intensity of the reaction decreases due to decrease of the iron / aluminum contact area and the content of aluminum [21].…”
Section: Resultsmentioning
confidence: 99%
“…So FeAlbased functional materials such as cellular filter not only broaden their applications, but also make the mechanical properties not an important issue. Our recent studies [14][15][16] have demonstrated that porous Fe-Al and Ti-Al structures can be fabricated through reactive syntheses of commercial Fe and Al or Ti and Al mixed powders based on the Kirkendall effect and used for the filtration purposes. The aim of this paper is to report a detailed study of the influence of the preparation parameters on the synthesis of porous FeAl alloy, in order to obtain the optimal parameters to synthesize porous FeAl alloy with controllable pore structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous intermetallics, which include Ti-Al, Fe-Al and Ni-Al, have been fabricated in our previous work by reactive synthesis using element powders as raw materials [1][2][3][4]. Among the new porous materials with B2 structure, porous FeAl intermetallics present certain unique physical, chemical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Many techniques have been applied to produce porous Ti and its alloy implants in recent years. [6][7][8][9][10] Nevertheless, there are still problems to be solved in the field of porous Ti for biomedical applications [11] : the difficulty to create controlled porosity and pore sizes, the insufficient knowledge of porous structureproperty relationships, the requirements of new sintering techniques with rapid energy transfer, and less energy consumption and so on.Spark plasma sintering (SPS) as one of the field assisted sintering techniques, is a relative new sintering technique for PM and ceramics. SPS is a high efficient and energy saving powder consolidation and sintering technology capable of processing conductive and non-conductive materials.…”
mentioning
confidence: 99%